An Update on the Bird Population in Gaya Island - Emily A. Gilbert; Jephte Sompud; Oswald A. Igau; Maklarin Lakim; Rimi Repin; Alim Biun (e-VIBS, Faculty of Science and Natural Resources, 2018)
The ecosystem of small islands also plays a crucial role in serving as a habitat for birds especially the endemic and migratory birds. To date, there is still limited study that has been done in documenting the avian community in small islands such as Gaya Island in Sabah. Hence, this study aims to document and update the bird population by looking at the species richness and abundance of birds in Gaya Island. The method that was being used was solely standard point count method in three selected sampling trails for six months of survey. A total number of 524 individuals from 26 species and 17 families were recorded of which adding 16 species of birds from the past study. The value of the Shannon Wiener index and Simpson diversity index for the diversity of birds were 2.607 and 0.906 respectively. Interestingly two endemic species, two near threatened and one vulnerable species namely Philippine Megapode (Megapodius cumingii), White-crowned Shama (Copsychus strickladii), White-chested Babbler (Trichastoma rostratum), Grey-chested Jungle Flycatcher (Rhinomyias umbratilis) and Great Slaty Woodpecker (Mulleripicus pulverulentus) were sighted during the survey. The result from this study showed that Gaya Island supports diverse species of birds and play a crucial transit location for migratory bird species. Hence, it indicates for the need of further bird conservation studies in the island.